Rootstocks resistant to Meloidogyne incognita and compatibility of grafting in net melon - Galatti, Francine de Souza [UNESP]; Franco, Alexandre Junqueira [UNESP]; Ito, Letícia Akemi [UNESP]; Charlo, Hamilton de Oliveira; Gaion, Lucas Aparecido [UNESP]; Braz, Leila Trevisan [UNESP] (FapUNIFESP (SciELO), 2013)
Due to the few studies about grafting in net melon, in order to obtain better control of soil pathogens, the aim of the present study was to evaluate 16 genotypes of Cucurbitaceae: Benincasa hispida, Luffa cylindrica, pumpkin 'Jacarezinho', pumpkin 'Menina Brasileira', squash 'Exposição', squash 'Coroa', pumpkin 'Canhão Seca', pumpkin 'Squash', pumpkin 'Enrrugado Verde', pumpkin 'Mini Paulista', pumpkin 'Goianinha', watermelon 'Charleston Gray', melon 'Rendondo Gaucho', melon 'Redondo Amarelo', cucumber 'Caipira HS' and cucumber 'Caipira Rubi', regarding to compatibility of grafting in net melon and resistance to Meloidogyne incognita, based on the reproduction factor (RF), according to Oostenbrink (1966). To assess resistance, the seedlings were transplanted to ceramic pots and inoculated with 300/mL eggs and/or second stage juveniles of M. incognita. At 50 days after transplanting, the plants were removed from the pots and the resistance was evaluated. The compatibility between resistant rootstock and grafts of net melon was determined by performing simple cleft grafting, in a commercial net melon hybrid of great market acceptance and susceptible to M. incognita (Bonus no. 2). The genotypes Luffa cylindrica, pumpkin 'Goianinha', pumpkin 'Mini-Paulista', melon 'Redondo Amarelo', watermelon 'Charleston Gray' are resistant to the nematode M. incognita. The better compatibilities occurred with the rootstocks melon 'Amarelo', which presented 100% of success, followed by pumpkin 'Mini-Paulista' with 94%. On the other hand, Sponge gourd, watermelon 'Charleston Gray' and pumpkin 'Goianinha' showed low graft take percentages of 66%, 62% and 50%, respectively.
Keywords: Cucumis melo var. reticulatus; Cucurbitaceae; Nematode; Plant diseases